Metodología para la selección y desarrollo del producto comercial inmobiliario como aspecto fundamental de la estructuración de proyectos de construcción (2020)
Construction is one of the most incident industries in the world economy and in Colombia. This, only in its branch of real estate construction, came to contribute approximately 9% of GDP in 2019 (La República, 2020), with accumulated sales of {dollar} 12.7 billion pesos in the first 100 companies (Dinero Magazine, 2020) . However, increases in land values, policies and legislation associated with housing, and the maturing of the market have generated significant challenges in structuring real estate construction projects that seek to generate value, creating new barriers that force organizations to implement technology, methodologies and processes that guide the development of projects to mitigate the uncertainty and risk associated with them. This degree work will carry out a study of the antecedents, conditions, restrictions and good practices used in the definition of the products proposed in the structuring of real estate projects, with the purpose of proposing a methodology that allows the selection and development of said products in pro of the associated decisions towards determining the viability of a project, based on its ability to generate value. The study of technical, normative, legal, commercial and financial factors that play an important part in the industry, as well as all other differentiating aspects of it, will be carried out for the purpose of supporting the methodology proposed in this thesis.